Medical Education Breakthroughs: What Constitutes Milestones in Curriculum, Teaching and Assessment? (Canadian Medical Education Journal, 2010)
Medical Education Breakthroughs: What Constitutes Milestones in Curriculum, Teaching and Assessment?